Post-translational modifications: How to modulate Rab7 functions. (3rd May 2020) - Modica, Graziana; Lefrancois, Stephane
ABSTRACT: The small GTPase Rab7 is the main regulator of membrane trafficking at late endosomes. This small GTPase regulates endosome-to-trans Golgi Network trafficking of sorting receptors, membrane fusion of late endosomes to lysosomes, and autophagosomes to lysosomes during autophagy. Rab7, like all Rab GTPases, binds downstream effectors coordinating several divergent pathways. How cells regulate these interactions and downstream functions is not well understood. Recent evidence suggests that Rab7 function can be modulated by the combination of several post-translational modifications that facilitate interactions with one effector while preventing binding to another one. In this review, we discuss recent data on how phosphorylation, palmitoylation and ubiquitination modulate the ability of this small GTPase to orchestrate membrane trafficking at the late endosomes.